Functional GnRH receptor signaling regulates striatal cholinergic neurons in neonatal but not in adult mice - Farkas, Imre; Skrapits, Katalin; Sárvári, Miklós; Göcz, Balázs; Takács, Szabolcs; Rumpler, Éva; Hrabovszky, Erik (Frontiers in Endocrinology, 2024)
Reproduction in mammals is controlled by hypothalamic gonadotropin-releasing hormone (GnRH) neurons. Recent studies from our laboratory established that the basal ganglia of the human brain contain additional large populations of GnRH synthesizing neurons which are absent in adult mice. Such extrahypothalamic GnRH neurons mostly occur in the putamen where they correspond to subsets of the striatal cholinergic interneurons and express GnRHR autoreceptors.In an effort to establish a mouse model for functional studies of striatal GnRH/GnRHR signaling, we carried out electrophysiological experiments on acute brain slices from male transgenic mice. Using PN4-7 neonatal mice, half of striatal ChINs responded with transient hyperpolarization and decreased firing rate to 1.2 µM GnRH, whereas medium spiny projection neurons remained unaffected. GnRH acted on its specific receptor because no response was observed in the presence of the GnRHR antagonist Antide. Addition of the membraneimpermeable G protein-coupled receptor inhibitor GDP-β-S to the internal electrode eliminated the effect of GnRH. Further, GnRH was able to inhibit ChINs in presence of tetrodotoxin which blocked action potential mediated events. Collectively, these data indicated that the receptor underlying the effects of GnRH in neonatal mice is localized within ChINs. GnRH responsiveness of ChINs was transient and entirely disappeared in adult mice.These results raise the possibility to use neonatal transgenic mice as a functional model to investigate the role of GnRH/GnRHR signaling discovered earlier in adult human ChINs.